Comparison of the Cardiovascular hemodynamic adaptations of angina pectoris to "second wind" - Motto, Rosemary E. (My University, 1979)
Heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP ), rate-pressure product (RPP), the mean maximal MET level and the mean maximal painfree MET capacity were studied in 38 patients with exertional angina pectoris (AP) due to coronary occlusive disease. The investigative conditions were at rest and during two maximal graded exercise tests, separated by a 10 minute walk at a workload of 1.5 mph with a 0% grade. The data that were collected from each S were analyzed by student's t-test for paired means. Mean maximal MET level increased from 3.64 on first effort to 4.38 on second effort. Mean painfree MET capacity increased from 2.97 to 3.85 on second effort. Maximum HR increased from 131 bpm, maximum SBP decreased from 166 mmHg to 163 mmHg, maximum RPP increased from 220 to 228 and maximum DBP decreased from 84.4 to 82.1. At the MET level provoking AP on first effort, HR on second effort was unchanged, RPP was decreased from 227 to 220, SBP was decreased from 168.6 to 163, and the DBP was decreased from 84.6 to 81.9. The observed increase in musculoskeletal performance and cardiac work capacities may be explained by enhanced arteriolar dilation or by augmentation of the peripheral circulation as seen by dilatation of the conductance vessels.
Keywords: Hemodynamics; Angina pectoris